2016
DOI: 10.1161/jaha.116.003270
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sleep‐Disordered Breathing on Long‐Term Outcomes in Patients With Acute Coronary Syndrome Who Have Undergone Primary Percutaneous Coronary Intervention

Abstract: BackgroundSleep‐disordered breathing (SDB) has been recognized as an important risk factor for cardiovascular diseases; however, the impact of SDB on long‐term outcomes in patients with acute coronary syndrome has not been fully evaluated.Methods and ResultsWe performed overnight cardiorespiratory monitoring of 241 patients with acute coronary syndrome who were successfully treated with primary percutaneous coronary intervention between January 2005 and December 2008. The presence of SDB was defined as apnea–h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 22 publications
(43 reference statements)
2
33
0
2
Order By: Relevance
“…Several small observational studies have demonstrated the association between OSA and increased risk of adverse outcomes following ACS 12–14. Our study extends prior analysis by focusing on the role of OSA in a high-risk subset of patients with DM.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Several small observational studies have demonstrated the association between OSA and increased risk of adverse outcomes following ACS 12–14. Our study extends prior analysis by focusing on the role of OSA in a high-risk subset of patients with DM.…”
Section: Discussionsupporting
confidence: 62%
“…Obstructive sleep apnea (OSA) is an increasingly recognized chronic disorder in patients with ACS, with reported incidence of 36% to 63% across various ethnicities 8. Recent evidence indicates OSA initiates and exacerbates coronary atherosclerosis,9–11 and predicts adverse cardiovascular outcomes post-ACS in the long run 12–16. Also, studies have shown the potential interaction between OSA and DM in glycemic control and the development of chronic diabetic complications 17–20.…”
Section: Introductionmentioning
confidence: 99%
“…Среди пациентов с ИБС, как правило, более высокий уровень смертности -у больных с острым коронарным синдромом. В исследовании, опубликованном T. Mazaki et al в 2016 г., коморбидность СОАС с острым коронарным синдромом была обнаружена у 52,3% больных [27]. Всем пациентам проводили первичное чрескожное коронарное вмешательство.…”
Section: основныеunclassified
“…Several studies have also reported that the presence of OSA can have a prognostic impact on patients with CVD. For instance, the co-existence of OSA with: stable coronary artery disease (CAD), acute coronary syndrome (ACS), acute myocardial infarction (MI) and HF, is associated with an increased risk of CV mortality and morbidity (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%